Giant submandibular gland duct sialolith mimicking an impacted canine tooth - Bhullar, Ramandeep Singh (Natl J Maxillofac Surg, 2015)
Sialolithiasis is the most common disease affecting the salivary glands and accounts for 80% of salivary gland disorders. Chronic sialolithiasis promotes stone formation. Size of the salivary stones may range from 0.1 mm to 30 mm or be even bigger. Those salivary stones, the size of which exceeds 15 mm in any one dimension or 1 g in weight are classified as giant sialoliths. Giant sialoliths of the submandibular gland duct are rarely reported. Here, we report a case of a giant sialolith of the submandibular gland duct mimicking an impacted mandibular canine tooth on routine radiographic examination and its surgical management through an intraoral approach.